ANALISIS KINERJA KEUANGAN KOPERASI KELUARGA TRIDINANTI PALEMBANG - Aida Rakhmawati; Yusro Hakimah; Hasyunah Hasyunah (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
Cooperatives need tools to determine the financial performance of cooperatives so that cooperative management can carry out their duties and obligations properly in accordance with the objectives of cooperatives in general. As a general guideline in knowing financial performance, it is necessary to have financial reports issued by cooperatives, to find out the success and problems experienced by cooperatives in managing their finances. The purpose of this study was to determine and analyze the financial performance of the Tridinanti Family Cooperative in 2015-2020. The type of data used is secondary data with data collection techniques in the form of financial balance reports and reports of remaining operating results. The results of the study concluded that the performance of the Tridinanti Family Cooperative for the last six years, from 2015 to 2020, was generally very good. Keywords: Cooperative financial performance